Comparative assessment of diagnostic accuracy: Helicobacter pylori stool antigen test versus rapid urease test in adult patients with upper gastrointestinal symptoms - Mohamed Fakhry; Khaled Abdelazeem; Mona M. Abdelmeguid; Mahmoud A. Abdelmaksoud; Emad Abdelrazzak; Omran M. Abdelmola; Safwat Salama; Waleed S. EL-Nasser; Maha Mohamed; Mohamed A. Younes; Amro M. Hassan (Al-Azhar Assiut Medical Journal)
Background and aim Helicobacter pylori (H. pylori) is the leading cause of human stomach infections. Accurate diagnosis is ucial for the effective management of H. pylori, leading to the eation of numerous diagnostic techniques, including both invasive and noninvasive methods. Methods This study thoroughly examines the diagnostic accuracy of the H. pylori Stool Antigen (HpSA) test in comparison to the rapid urease test (RUT). Background and aim HpSA test, known for being non-invasive, cost-effective, and quick, is contrasted with the fast but invasive RUT. Conducted on 100 adult patients from June to December 2022, the study utilized a comprehensive diagnostic approach, including medical history evaluations, physical exams, abdominal ultrasounds, laboratory tests, and careful stool sample collection. Additionally, all participants underwent RUT, stool antigen tests, and histopathology examinations. Results The findings revealed that the HpSA test identified more positive H. pylori cases (73) than the RUT (59) (P<0.01). Although RUT results closely matched histopathology outcomes, both RUT and histopathology showed greater accuracy than HpSA. Furthermore, RUT demonstrated higher sensitivity (98.2%) and accuracy (98.3%) compared with HpSA, while specificity was similar for both tests. Conclusion The HpSA test is a straightforward and noninvasive diagnostic method that is easy to use in laboratory settings. On the other hand, the RUT is known for its high accuracy and sensitivity. Together, these characteristics make the HpSA test a valuable alternative for diagnostic purposes.